Manajemen Keuangan Sekolah Dasar: Kajian Literatur - Dessy Fitria; Anis Choirun Niswah; M. Nizar Sofan (DIDAKTIKA, 2025)
One of the important elements in educational management is financial management, which is directly related to the success and achievement of educational organizations. Planning, implementation, bookkeeping, supervision, and accountability are all part of financial management work. According to Article 48 of Law No. 20 of 2003, the management of education funds must be based on the principles of efficiency, effectiveness, transparency, justice, and accountability. Financial management aims to prevent the misappropriation of educational funds by enhancing effectiveness, efficiency, accountability, and transparency. The objective of this research is to identify and analyze financial management procedures in elementary schools. To achieve this objective, this research analyzes how these theories correlate with the reality on the ground. The research results indicate that the six surveyed elementary schools manage their finances in accordance with financial management principles and the applicable government policies. From planning to supervision, financial management is carried out in a structured manner. Education funds are used based on the RKAS that has been mutually agreed upon.